2017
DOI: 10.1016/j.acalib.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Where Students Start and What They Do When They Get Stuck: A Qualitative Inquiry into Academic Information-Seeking and Help-Seeking Practices

Abstract: This study investigates two questions key to academic library resources and services: Which sources are students most likely to use to begin their academic work? Whom do students tend to consult for research assistance? Indepth interviews conducted with 15 undergraduate and graduate students were thematically analyzed through a three-step process. The findings indicate that students are most likely to consult faculty and peers for assistance and are largely unaware of librarians' roles, while they tend to begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
1
15
0
4
Order By: Relevance
“…This should perhaps include peer support schemes and group work activities, as being among individuals with equal status (age, the level of study) reduces stigma (Winograd & Rust, 2014). Additionally, as some students feel more comfortable with their classmates rather than tutors, it is valuable to offer group work activities in order to encourage participation and promote the process of asking questions and, later on, academic help (Thomas et al, 2017).…”
Section: International Journal Of Educationmentioning
confidence: 99%
“…This should perhaps include peer support schemes and group work activities, as being among individuals with equal status (age, the level of study) reduces stigma (Winograd & Rust, 2014). Additionally, as some students feel more comfortable with their classmates rather than tutors, it is valuable to offer group work activities in order to encourage participation and promote the process of asking questions and, later on, academic help (Thomas et al, 2017).…”
Section: International Journal Of Educationmentioning
confidence: 99%
“…Google) et du catalogue de leur bibliothèque universitaire. Cette primauté des bases de données rejoint les résultats de l'étude de Thomas et al (2017) où la plupart des doctorants ont déclaré que les bases de données représentaient leur principale source d'information. Cependant, l'usage aussi fréquent de moteurs de recherche comme Google chez les étudiants de notre enquête indique qu'ils semblent faire preuve d'une approche complémentaire dans leurs recherches.…”
Section: Outil De Prédilection Pour Chercher De L'informationunclassified
“…D'autre part, cette répartition du sentiment d'autoefficacité permet de relever un besoin de formation pour la majorité des étudiants afin d'améliorer leur utilisation des bases de données documentaires dans le cadre de leurs recherches d'information. De ce fait, maîtriser l'usage des bases de données représente une compétence-clé aux études supérieures puisqu'elles sont souvent un des premiers outils de recherche d'information employés par les étudiants (Thomas et al, 2017). De plus, même si certains étudiants amorcent leurs recherches d'information sur Google, il reste que leurs quêtes mènent souvent à des bases de données dont l'accès est rendu possible par les services électroniques de la bibliothèque de leur établissement.…”
Section: Niveau D'expertise Par Rapport à L'utilisation Des Bases De unclassified
“…One student talked with the professor before or after class: "If there was ever a theory that I was confused on, … he [would walk] me through what to do … about the problem until I understood why." Other studies have also found that students often turn to their professor for help before or instead of librarians, typically because of the relationship they already have established (Head & Eisenberg, 2009;Miller & Murillo, 2011;Thomas, Tewell, & Willson, 2017).…”
Section: Student Strategiesmentioning
confidence: 99%